2022
DOI: 10.3390/diagnostics12061473
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heart Failure, 90-Day Mortality, and Gravitational Ischemia in the Brain

Abstract: During the 90 days following hospitalization for acute heart failure, the ejection fraction and type of discharge medications have been shown in clinical trials to have little effect on mortality. We examined the recent literature addressing brain-related etiologies of sudden death following heart failure. Two mechanisms of sudden unexpected death have been suggested to possibly result from four significant influences on pathophysiology in the brain. The two causes of sudden death are (1) severe cardiac arrhyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…In conclusion, the CVT Late Seizure Investigators [1] reported important findings from their systematic review, which were potentially consistent with the findings of other recent papers [2][3][4][5] to the extent of supporting further research into a possible relationship between late seizures following CVT, cerebro-vascular inflammatory mechanisms, and gravity in the brain.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…In conclusion, the CVT Late Seizure Investigators [1] reported important findings from their systematic review, which were potentially consistent with the findings of other recent papers [2][3][4][5] to the extent of supporting further research into a possible relationship between late seizures following CVT, cerebro-vascular inflammatory mechanisms, and gravity in the brain.…”
supporting
confidence: 81%
“…The CVT Late Seizure Investigators concluded, in part, that further high-quality studies are warranted to develop predictive models for individualized risk stratification and prediction of CVT late seizures [1]. However, the overall literature about CVT suggests that important resources in that regard may include autopsy studies [2], combined with studies of systemic biological markers [3], and observations about gravity in the brain [4,5].…”
mentioning
confidence: 99%
See 3 more Smart Citations